Assessment of motivation to control alcohol use: The motivational thought frequency and state motivation scales for alcohol control. (August 2016) - Robinson, Nicole; Kavanagh, David; Connor, Jason; May, Jon; Andrade, Jackie
Abstract: Introduction: The Elaborated Intrusion Theory of Desire holds that desires for functional and dysfunctional goals share a common form. Both are embodied cognitive events, characterised by affective intensity and frequency. Accordingly, we developed scales to measure motivational cognitions for functional goals (Motivational Thought Frequency, MTF; State Motivation, SM), based on the existing Craving Experience Questionnaire (CEQ). When applied to increasing exercise, MTF and SM showed the same three-factor structure as the CEQ (Intensity, Imagery, Availability). The current study tested the internal structure and concurrent validity of the MTF and SM Scales when applied to control of alcohol consumption (MTF-A; SM-A). Methods: Participants ( N  = 417) were adult tertiary students, staff or community members who had recently engaged in high-risk drinking or were currently trying to control alcohol consumption. They completed an online survey comprising the MTF-A, SM-A, Alcohol Use Disorders Identification Test (AUDIT), Readiness to Change Questionnaire (RCQ) and demographics. Results: Confirmatory Factor Analysis gave acceptable fit for the MTF-A, but required the loss of one SM-A item, and was improved by intercorrelations of error terms. Higher scores were associated with more severe problems on the AUDIT and with higher Contemplation and Action scores on the RCQ. Conclusions: The MTF-A and SM-A show potential as measures of motivation to control drinking. Future research will examine their predictive validity and sensitivity to change. The scales' application to both increasing functional and decreasing dysfunctional behaviours is consistent with EI Theory's contention that both goal types operate in similar ways. Highlights: We tested measures of frequency and current state of motivation for alcohol control. Confirmatory Factor Analyses gave acceptable fit from a 3-factor model. This model was the same as ones previously obtained on alcohol craving measures. The study confirms the role of intensity, imagery and availability in motivational cognitions. Positive correlations of all factors with readiness to change and alcohol problems were seen.